XML Schema may not always be the right tool for the job some things to consider as you put XML Schema to use. - Wacey, Michael (SOA webservices journal.)
Will many of the features in XML Schema be widely used? In particular, I agree that it is better to have an XML language for specifying document layout rather than the DTD language. On the other hand, I am not sure that the document layout should be strongly typed. The nightmare scenario is where a customer cannot place a large order because an XML document is invalid. Assume a company has an average order size of 50,000 dollars with a current order range of 3,000 to 220,000. It would be reasonable to set a criterion in the Purchase Order Schema for this company to set a total order rage of Zero to One Million. At some point in the future, after price increases and business changes, a large customer may place an order for 1,020,000. The Purchase Order document would be rejected as invalid.